RELATION OF ENDOMETRIAL PATHOLOGICAL CHANGES WITH ENDOCRINE DISORDERS AND METABOLIC SYNDROME - Kocevska, Ana; Zafirov, Dimce; Petrusevska, Gordana; Skeparovska, Kristina; Zafirova, Biljana; Stratrova, Slavica Subeska (Journal of Morphological Sciences; Vol 4 No 2 (2021): JMS, 2021)
Endometrial hyperplasia (EH) is an abnormal proliferation of endometrial glands and stroma and is associated with an increased risk of endometrial cancer (EC). Risk factors such as obesity, chronic anovulation, late menopause, hypertension, and diabetes lead to an increased risk of EH and EC. Aim: to determine the association of pathological changes in the endometrium with endocrine disorders and metabolic syndrome in women in peri and postmenopause. This study including a total of 139 patients in peri and postmenopause.  The examined group consisted of 104 women with fractional explorative curettage due to a medical indication and was divided into two subgroups: peri and postmenopausal. The control group included 35 healthy women. Anamnestic data, body weight, height, blood pressure measurement, were taken from all patients, and the following laboratory parameters were determined: glucose, TSH, thyroxine, glycosylated hemoglobin (HbA1c), and Vitamin D . The presence of metabolic syndrome (MetS) according to its diagnostic criteria was also determined. In our study, significance was found in the comparison of the examined and the control group (p = 0.0001) in addition to the significantly higher BMI in the examined group. The comparison also  indicated the existence of a significant difference in the level of glycemia in addition to a significantly higher level in the examined group (p = 0.0001). The statistical analysis did not indicate a significant difference between the two subgroups of the examined group, nor between the examined and the control group in terms of TSH, thyroxine and HbA1c levels. The value of vit. D was significantly higher in the control than  in the study group (p = 0.0001). The analysis showed that patients with fractional explorative curettage had 4.982 times [OR = 4.982 (2.06â€“12.02) 99% CI] significantly more often MetS compared to women in the control group. Patients in the examined group had a significantly higher BMI, glycemia, and more frequent presence of MetS than those in the control group. Keywords : endometrium, risk factors, fractional explorative curettage, metabolic syndrome https://doi.org/10.55302/JMS2142156k